Cost-Effectiveness Analysis of Pembrolizumab in Patients With Advanced Esophageal Cancer Based on the KEYNOTE-181 Study - Zhan, Mei; Xu, Ting; Zheng, Hanrui; He, Zhiyao (Frontiers in Public Health, 2022)
Background and purpose: The KEYNOTE181 study demonstrated that pembrolizumab for advanced or metastatic esophageal cancer in patients with PD-L1 CPS ≥10 had a survival advantage and better tolerability than chemotherapy, but at the same time, pembrolizumab places an economic burden on patients. This study assessed the cost-effectiveness of pembrolizumab based on the KEYNOTE181 study. Materials and methods: A three-state Markov model (progression-free survival [PFS], progressive disease [PD] and death) based on data from the KEYNOTE181 study was used to estimate the incremental cost-effectiveness ratio (ICER) of pembrolizumab versus chemotherapy for advanced or metastatic esophageal cancer. The model evaluates the outcomes from the Chinese society’s perspective. Costs, quality-adjusted life-years (QALYs), and the ICER in terms of 2021 US$ per QALY gained, were calculated. one-way and probabilistic sensitivity analyses were performed to evaluated the model robustness. Results: Compared with chemotherapy, pembrolizumab increased costs by $37,201.68, while gaining 0.23 QALYs, resulting in an ICER of $163,165.26 per QALY in patients with PD-L1 CPS≥10. The ICER $202,708.62 per QALY and $163,643.19 per QALY in total population and patients with esophageal squamous cell carcinoma, respectively. The ICER was much higher than the commonly accepted willingness-to-pay threshold ($11,105.80 per QALY). One-way and sensitivity analyses showed that the costs of pembrolizumab and the utility of PD were the crucial factors in determining the ICER, and probabilistic sensitivity analyses demonstrated pembrolizumab is unlikely to be cost-effective at a willingness-to-pay threshold of $11,105.80 per QALY. The result was robust across sensitivity analyses. Conclusion: Pembrolizumab is not a cost-effective treatment option for the second-line treatment of esophageal cancer from the perspective of Chinese society.